2003
DOI: 10.1023/a:1025461421791
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sexual homicides committed by psychopathic and nonpsychopathic offenders.

Abstract: In this study, the relationship between psychopathy and the perpetration of sexual homicide was investigated. The official file descriptions of sexual homicides committed by 18 psychopathic and 20 nonpsychopathic Canadian offenders were coded (by coders unaware of Psychopathy Checklist-Revised [PCL-R] scores) for characteristics of the victim, victim/perpetrator relationship, and evidence of gratuitous and sadistic violent behavior. Results indicated that most (84.7%) of the sexual murderers scored in the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
138
3
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(168 citation statements)
references
References 32 publications
(31 reference statements)
15
138
3
5
Order By: Relevance
“…According to some research results, proactive aggression is associated with delinquent and antisocial behaviors (Fite et al, 2008b;Raine et al, 2006;Scarpa et al, 2010;Vitaro et al, 2006), and psychopathic tendencies (Cornel et al, 1996;Porter et al, 2003;Woodworth and Porter, 2002). Some research indicates that reactive aggression is not directly associated with delinquency (Raine et al, 2006;Vitaro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to some research results, proactive aggression is associated with delinquent and antisocial behaviors (Fite et al, 2008b;Raine et al, 2006;Scarpa et al, 2010;Vitaro et al, 2006), and psychopathic tendencies (Cornel et al, 1996;Porter et al, 2003;Woodworth and Porter, 2002). Some research indicates that reactive aggression is not directly associated with delinquency (Raine et al, 2006;Vitaro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…20,152,153 In extreme cases-for example, among serial killers-comorbidity of psychopathy and sadistic personality is very high. [154][155][156][157] In their PCL-R study of murderers, Porter et a1 153 concluded…”
mentioning
confidence: 99%
“…18 A study that does provide a more detailed definition defines gratuitous violence as 'excessive violence that went beyond the level that would be necessary to accomplish the homicide and/or caused the victim unnecessary pain and suffering.' 19 Another study indicates that the term is used 'if the amount of violence clearly exceeded the degree of force that that would have been necessary to merely control the victim.' 20 In the latter definitions violence is not gratuitous if it seems to be necessary to carry out a certain crime (the principal offence), but comes to be seen as gratuitous once it goes beyond that which is necessary for this purpose.…”
Section: Objective Definitions Of Gratuitous Violencementioning
confidence: 99%
“…They also suggest that 'thrill seeking' may be a factor in some psychopathic violence. 42 However, as indicated, it is not only these instrumental or expressive motives that characterise psychopathic violence, but also that it is 'unemotional' and 'cold-blooded'. Psychopaths 'consistently commit more violence' and 'perpetrated the most severe … acts of physical abuse.'…”
Section: An Absence Of Empathymentioning
confidence: 99%